ANJİYOGENEZİN TEMEL MOLEKÜLER MEKANİZMALARI VE TÜMOR ANJİYOGENEZİ - KONUKOĞLU, Dildar; TURHAN, Mehtap Sultan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Angiogenesis is a term that describes the formation of new capillaries from a preexisting vasculature. This process is very important in physiologic conditions. It helps healing injured tissues, and in female population it helps forming the placenta after fertilization and reconstructs the inside layer of the uterus after menstruation. When the balance between proangiogenic and antiangiogenic factors is disturbed, angiogenesis is not controlled. This status may be important in tumor metastasis. In the review, we considered the molecular basis of angiogenesis and tumor angiogenesis.